Becoming ‘Swiss’: waste management integration among Ethiopian and Eritrean migrants in Zürich, Switzerland - Tucho, Gudina Terefe; Kalina, Marc; Tilley, Elizabeth (Frontiers in Sustainability, 2024)
For Swiss cities, connecting new migrants to basic services, like waste management, has emerged as an essential challenge toward their social and civic integration. Drawing on an ethnographic approach, this study investigates solid waste management integration within Zürich’s Ethiopian and Eritrean migrant communities. Our findings suggest that new arrivals learn quickly and are driven by a motivation to integrate and adapt to expected norms. However, learning is often characterized by trial and error and accompanied by expensive mistakes. Barriers include a lack of translated informational material and insufficient opportunity for asylum seekers to learn rules and norms on waste management. We recommend making standardized materials available and ensuring clear communication in a language that newly arriving migrants can understand. We also recommend targeted training on life skills, including waste management behaviors for asylum seekers at residential processing centers so that refugees can be trained on expected norms before transitioning into an independent living situation.